1998
DOI: 10.4095/209965
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphism of hydrothermally altered rocks

Abstract: In some metamorphosed volcanic belts, evidence of premetamorphic hydrothermal activity is preserved in the form of distinct metamorphic mineral assemblages. By considering the effect of metamorphism on rocks of various compositions, it is possible to deduce premetamorphic mineral assemblages, some of which could be products of hydrothermal alteration. In some rocks, precursor minerals kaolinite, muscovite, and chlorite would indicate aluminous, potassic, and ferromagnesian alteration, respectively. The stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the first place, distinction between unaltered felsic volcanic rocks or tuffs from granite is not obvious when these rocks are transformed into gneisses. In addition, common types of hydrothermal alteration (e.g., argillic, sericitic, and ferromagnesian) in submarine environments lead to chemically modified rocks, the metamorphic products of which are commonly misinterpreted as metapelites (e.g., Hodges and Manojlovic 1993;Froese 1998). However, it has been shown that in high-grade metamorphic belts, diagnostic features of volcanic protoliths and their hydrothermally altered products may still be revealed by careful examination of rock associations, petrography, and geochemistry (Gifkins et al 2005;Bonnet and Corriveau 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the first place, distinction between unaltered felsic volcanic rocks or tuffs from granite is not obvious when these rocks are transformed into gneisses. In addition, common types of hydrothermal alteration (e.g., argillic, sericitic, and ferromagnesian) in submarine environments lead to chemically modified rocks, the metamorphic products of which are commonly misinterpreted as metapelites (e.g., Hodges and Manojlovic 1993;Froese 1998). However, it has been shown that in high-grade metamorphic belts, diagnostic features of volcanic protoliths and their hydrothermally altered products may still be revealed by careful examination of rock associations, petrography, and geochemistry (Gifkins et al 2005;Bonnet and Corriveau 2007).…”
Section: Introductionmentioning
confidence: 99%